The Pacific Alliance: Towards the path of integration? ¿Towards the Integration Way? - Godoy López, Víctor Alejandro (2016)
Historically, Latin American countries have not had strong relations with Asia as a consequence of their international relations directing towards the Western hemisphere; this is a result of Latin American countries, upon gaining independence from Spain having been influenced first by England and then by United States. Indeed, save a few exceptions such as Chile and Peru, it was only in the early 1990s that Latin America and Asia Pacific began to improve trade relations. The Latin American region began to see Asia as a possible economic model an alternative for the diversification of its foreing policy.